A PENGARUH METODE LEARNING STARTS WITH A QUESTIONS TERHADAP MINAT BELAJAR BAHASA INDONESIA SISWA KELAS V SD NEGERI 13 BIRU KABUPATEN BONE - Awal Nusantara; Hafid, Abd; Muliadi (MACCA : Science-Edu Journal, 2024)
This research is a pre-experimental type of quantitative research which aims to determine the interest in learning Indonesian for class V students at SD Negeri 13 Biru, Bone Regency and the influence of the Starts With A Questions Learning Method on the interest in learning for class V students at SD Negeri 13 Biru, Bone Regency. The variables in this research are the Learning Starts With A Questions method (independent variable) and students' learning interest (dependent variable). The population in this study was 48 class V students at SD Negeri 13 Biru. The sampling technique in this research used non-probability sampling in the form of saturated sampling. Research data was obtained by distributing questionnaires describing students' learning interests and documentation. The data collection techniques used were pretest and posttest. The data analysis technique is descriptive and inferential analysis using Nonequivalent Control Group Design. The results obtained in this research are: There is a difference in the learning interest of class V students at SD Negeri 13 Biru before and after the Learning Starts With A Questions method, There is a significant influence of the Learning Starts With A Questions method on the learning interest of class V students SD Negeri 13 Biru.